2012
DOI: 10.1002/cta.1880
|View full text |Cite
|
Sign up to set email alerts
|

Realization of arbitrary current transfer functions based on commercially available CCII + s

Abstract: In this paper, a new topology for realizing arbitrary n th -order current transfer function (TF), consisting of only plus-type second-generation current conveyors (CCII+s), is suggested. The proposed TF simulator employs only grounded capacitors and is free from the passive element matching requirements. The developed TF simulator can be constructed directly with commercially available active components such as AD844s. It has low-input and high-output impedances, a feature which makes it fully cascadable with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This allows achieving a variable GBW or, in other words, the possibility of obtaining high gain levels without affecting the bandwidth of the electronic interface. One of the main downsides of using CCIIs is their lack of a low impedance voltage output terminal, making it cumbersome to use in a voltage mode processing chain [33][34][35][36][37][38]. Recently, a novel mixed-mode analog active block, named Second-generation voltage conveyor (VCII), has been proposed to overcome that limitation [15][16][17] and used in many applications [39][40][41][42][43].…”
Section: Electronic Interfacementioning
confidence: 99%
“…This allows achieving a variable GBW or, in other words, the possibility of obtaining high gain levels without affecting the bandwidth of the electronic interface. One of the main downsides of using CCIIs is their lack of a low impedance voltage output terminal, making it cumbersome to use in a voltage mode processing chain [33][34][35][36][37][38]. Recently, a novel mixed-mode analog active block, named Second-generation voltage conveyor (VCII), has been proposed to overcome that limitation [15][16][17] and used in many applications [39][40][41][42][43].…”
Section: Electronic Interfacementioning
confidence: 99%
“…On the other hand, if the output of the previous stage of the high input impedance circuit is current, it is necessary to use a resistor connected to the input of this circuit. Apart from these, CCIIs have been found wide practice realms in the literature 31–41 …”
Section: Introductionmentioning
confidence: 99%
“…Apart from these, CCIIs have been found wide practice realms in the literature. [31][32][33][34][35][36][37][38][39][40][41] In this manuscript, a new FWR employing a single dual output CCII (DO-CCII) is proposed. The proposed VM FWR topology with high input impedance uses three grounded resistors without any matching constraints.…”
mentioning
confidence: 99%
“…In the last two decades, there has been much interest in current‐mode (CM) circuits in view of their many advantages over the voltage‐mode (VM) circuits such as higher bandwidth, large dynamic range, lower power consumption, greater linearity, lower sensitivity, and better accuracy . As early as in 1971, Bhattacharyya and Swamy introduced the concept of transposition and showed that VM circuits can be converted to CM circuits and vice versa by simply replacing the non‐reciprocal elements by their transposes and retaining the reciprocal subnetwork part.…”
Section: Introductionmentioning
confidence: 99%